Human Dignity and Quantified Self: The Constitutional Challenge of AI (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
This essay examines the relevance of the constitutional concept of dignity in the digital society. This analysis examines how digital technologies are currently redefining the concept of human personality, employing a quantitative approach that considers human behavior through a statistical lens. The idea of dignity is then considered as a useful element for starting a new juridical reasoning aiming to draw a line of continuity through a person’s physical, psychic, relational, and even digital existence, and the EU AI Act seems to be the beginning of a new regulation intended to define a technological development that could be authentically anthropocentric.